If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x + 3) + -12x = 3x + 17 Reorder the terms: 7(3 + 2x) + -12x = 3x + 17 (3 * 7 + 2x * 7) + -12x = 3x + 17 (21 + 14x) + -12x = 3x + 17 Combine like terms: 14x + -12x = 2x 21 + 2x = 3x + 17 Reorder the terms: 21 + 2x = 17 + 3x Solving 21 + 2x = 17 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 21 + 2x + -3x = 17 + 3x + -3x Combine like terms: 2x + -3x = -1x 21 + -1x = 17 + 3x + -3x Combine like terms: 3x + -3x = 0 21 + -1x = 17 + 0 21 + -1x = 17 Add '-21' to each side of the equation. 21 + -21 + -1x = 17 + -21 Combine like terms: 21 + -21 = 0 0 + -1x = 17 + -21 -1x = 17 + -21 Combine like terms: 17 + -21 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| -8n=32 | | 0.15x+0.05(20-x)=0.10(22) | | 2x^2-5x+3=3 | | 0.80x+20.00=100 | | 2(10m-7a)+3(8a-3m)= | | 7(3x+4+2x)=63 | | 0.80x+20.00=281.60 | | y=-9/7x+2 | | x+14=29 | | 0=-100+(.7q-6)q | | 2(22-3*7)= | | 28-16=3(x-1) | | b+a=cx | | 2(x+6)=12+2x | | ln(2x^4+10x^3)+ln(1/(3x^3)) | | 7-6=12-2x | | 0=cx-a+b | | cx-a+b=2b | | 5x+-10=21-6x | | 9+x/2=10 | | 1x-4y=-27 | | y=5sinx+3x | | -4x/3=12 | | 355-5x=0+5x | | -3/4y+2=14 | | -2(3n-1)-n=5(n-4) | | 6/5+x=4/7 | | 120+10x=15+4x | | 2x+(2*2*x+5)=949 | | x-52=194 | | 5*5x=8*5 | | 6x-28=x-8 |